Can hydrogen economy help addressing regional economic inequalities: a regional hydrogen integration framework - Huang, Weizhao; Balta-Ozkan, Nazmiye (Elsevier, 2026)
Hydrogen is emerging as a cornerstone of global energy transitions, with its potential to drive economic growth and transform energy systems. As hydrogen can be produced by utilizing renewable resources and investing in production technologies, it has the potential to create new energy powers. The spatial nature of hydrogen systems in terms of where and how it is produced, stored, transported and used, means associated investments will have an impact on the economy and inherent regional inequalities within a nation. Using a systematic literature review, we find that there are comparatively fewer macroeconomic models that analyze the regional dimensions of the hydrogen transition than those examining national level impacts. By synthesizing our findings, we make the following contributions: (i) we show that the regional impacts of the hydrogen economy are realized through three mechanisms: the production method chosen, the hydrogen system segment a region hosts, and the geographic pattern of investment, (ii) we argue that whether these impacts alleviate or exacerbate regional inequalities is governed by two overarching forces: the spatial comparative advantage and local value creation capacity, (iii) we highlight that current macroeconomic models lack the spatial, technological and segmental resolution necessary to capture forward and backward linkages that hydrogen systems may instigate, pointing to the need for closer collaboration between regional scientists and engineers to understand how these opportunities and challenges may shape regional economies, and (iv) the conceptual framework we offer can help with supporting hydrogen’s role to alleviate regional inequalities by recognizing the interplay between economic, technological, and policy factors through three mechanisms, two overarching forces, and the feedback loops linking policy and distributive outcomes.
Keywords: 4406 Human Geography; 44 Human Society; Generic health relevance; 7 Affordable and Clean Energy; 13 Climate Action; 10 Reduced Inequalities; Hydrogen economy; Macroeconomic models; Industrial growth; Policy mechanisms; Hydrogen systems; Regional disparities; Regional growth; Regional economy